The integration of digital twin and serious game framework for new normal virtual urban exploration and social interaction - Sheng-ming Wang; Lan Hong Vu (Journal of Urban Management, 2023)
COVID-19 has disconnected humanity, reduced social interaction in physical urban areas, and led to the new normal, which describes the anticipated changes in human life and professionals due to the impact of the pandemic. In addition, as part of digital transformation, the post-pandemic New Normal includes accelerating digital solutions and new standards for virtual urban exploration and planning. This study applies the concept of digital twin and serious game design and uses Minecraft, a game-based platform that inspires creative, inclusive learning through play, for virtual urban exploration and the development of social interaction among participants. Dadaocheng, a historical area of Taipei city, is then studied as a case study with the Geoboxers application to develop the prototype for a co-creation experiment in Minecraft. The prototype development and the results of the experiment are then used in the Analytic Hierarchical Process (AHP) method to evaluate a set of influential criteria proposed in this study through pairwise comparisons by expert panelists. The results of the AHP analysis reveal users' simultaneous preferences for urban planning and social interaction with urban characteristics (22.14%), urban exploration (12.29%), and 3D models (11.97%). Subsequently, the research results showed a need to promote the integration of digital twins and serious game applications as digital tools for urban exploration and social interaction, increasing post-pandemic virtual urban planning and applying new urban design techniques. This study also contributes to the acceleration of digital transformation in urban planning and management.
Keywords: 710; COVID-19; Digital twin; New normal; Serious game; Urban planning; Virtual urban exploration and social interaction